Tindak Pidana Pencucian Uang dalam Bisnis Kripto: Analisis terhadap Celah Regulasi dan Pengawasan - Syahputra, Harry; Qomarudin, Heri; Suvinah, Suvinah (Postulat, 2025)
Crypto assets present a dualism as a financial technology innovation promising efficiency and economic potential, yet simultaneously opening new vulnerabilities to money laundering (ML) due to their decentralized and pseudo-anonymous nature. This phenomenon urges an analysis of the legal and supervisory framework in Indonesia. This study employs a qualitative approach with a normative juridical method, analyzing primary and secondary legislation as well as relevant literature. Primary data includes official government documents, while secondary data comprises books and scientific journals. The results indicate that ML modus operandi involving crypto in Indonesia includes techniques such as the use of nominees, unregulated VASPs, and potential exploitation of P2P transactions, as evidenced in actual cases. Although Indonesia has an AML/CFT legal framework (Law No. 8/2010) and updated sectoral regulations (POJK 27/2024) mandating KYC/CDD and the Travel Rule, the analysis identifies significant gaps. These gaps include limitations of primary laws in accommodating crypto specifics, challenges in implementing secondary regulations (Travel Rule, CDD effectiveness), technical difficulties in supervision and law enforcement (tracking anonymity, seizing digital assets), and gaps in implementing FATF international standards. The main conclusion is that the effectiveness of preventing and combating crypto ML requires strengthening adaptive regulations, enhancing institutional capacity, optimizing supervisory technology, and reinforcing domestic and international cooperation. Recommendations include regulatory harmonization, revision of relevant laws, continuous evaluation of POJK 27/2024, enhancement of technical and human resource capacities, strengthening inter-agency coordination, and developing risk mitigation strategies for P2P and unhosted wallets.